2022
DOI: 10.1210/clinem/dgac674
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Patients After Total Pancreatectomy and Islet Cell Autotransplantation at Off-Site Islet Isolation Facility

Abstract: Objective Total pancreatectomy with islet autotransplantation (TPIAT) is a definitive management for intractable pain in patients with chronic pancreatitis. Islet autotransplantation (IAT) allows for the preservation of beta-cells to prevent complications of long-term diabetes. Our study follows TPIAT recipients for up to 12 years to determine the procedure’s efficacy completed with an off-site islet isolation facility. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Transplantation of autologous human islets is considered a therapeutic option for the palliative treatment of chronic pain in people undergoing total pancreatectomy 44 45. Transplantation of human islets obtained from allogeneic, cadaveric pancreata has shown remarkable impact in restoring metabolic control in people with brittle type 1 diabetes worldwide 46.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of autologous human islets is considered a therapeutic option for the palliative treatment of chronic pain in people undergoing total pancreatectomy 44 45. Transplantation of human islets obtained from allogeneic, cadaveric pancreata has shown remarkable impact in restoring metabolic control in people with brittle type 1 diabetes worldwide 46.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that patients who have achieved insulin independence have been transplanted with a high proportion of islets. 30,32,37,53 As mentioned in the previous text, the islet isolation step is, therefore, an extremely critical step and should be performed with a skillful technique. The other associated factors include CP duration, 66 smoking, 32 and preoperative diabetes.…”
Section: P Os Toper Ative Manag Ementmentioning
confidence: 99%
“…Next, the explanted pancreas is returned to the original center for infusion into the patient 51 . Although CIT may worsen the transplantation outcomes with this procedure, remote TPAIT does not worsen islet isolation outcomes, insulin independence rate, and glycemic control 52,53 . Therefore, if a system for transporting the pancreas is developed, remote isolation can be conducted at centers without isolation facilities to facilitate TPAIT.…”
Section: Islet Isolation and Transplantationmentioning
confidence: 99%
See 1 more Smart Citation